EDUKASI PEMANFAATAN KOTORAN TERNAK UNTUK KELOMPOK WANITA TANI DESA SUKASIRNARASA – RANCAKALONG - SUMEDANG - Taofik, Ahmad; Fitriyyah, Ita (Universitas Negeri Surabaya, 2025)
Until now, livestock waste, both cows and sheep, in Sukasirnarasa Village has not been managed optimally, and in fact tends to be a source of environmental pollution. According to these condition, educational activities were carried out on the use of livestock manure through magot cultivation for the Kelompok Wanita Tani (KWT) in Sukasirnarasa Village, Rancakalong District, Sumedang Regency. The service method used is Community Based Participatory Research (CBPR). There were 40 (forty) KWT members who took part in this activity. The educational background of the participants was elementary school 9 people (22.5 %), junior high school 23 people (57.5 %), high school 7 people (17.5 %) and bachelor's degree 1 person (2.5 %). A total of 25 participants, equivalent to 62.5%, stated that they already knew about black soldier flies (BSF), while the remaining 15 people (37.5%) did not know. Twenty-eight participants (70%) stated that they did not know the potential of cow dung other than as fertilizer, and 29 people (72.5%) did not know the potential of BSF in bioconversion. Most of the participants provided very important answers to all the questions asked. The training activities and use of cow dung were enthusiastically attended by members of the Sukasirnarasa Village KWT